IMPACT OF ATRIAL FIBRILLATION ON THE NEAR AND LONG-TERM PROGNOSIS OF LIFE AFTER ACUTE MYOCARDIAL INFARCTION. THE DATA OF THE LIS-1 STUDY (LYUBERTSY MORTALITY STUDY OF PATIENTS WITH ACUTE MYOCARDIAL INFARCTION) - S. Yu. Martsevich; N. P. Kutishenko; M. L. Gynzburg; L. Yu. Drozdova; A. D. Deev; V. P. Smirnov (Рациональная фармакотерапия в кардиологии)
Aim. To study the effect of atrial fibrillation (AF) that existed before the myocardial infarction (MI), on near and long-term mortality in patients with acute MI.Material and methods. The data of LIS register (Lyubertsy study on mortality rate in patients after MI), that included all patients hospitalized for acute MI (n=1133) during the period from 1 January 2005 to 31 December 2007, were used to solve the aim of the study.Results. AF was recorded in 88 patients (7.8%), and the frequency of AF significantly increased with age. 22 patients with a history of AF (25%) died in hospital, and mortality in this group of patients was significantly higher than this in the whole group of patients (15.2%; p=0.025). However, these differences were not statistically significant when adjusted for age and gender (OR=1.25; 95% CI 0.77-2.04; p=0.37). 66 people from 961 patients, who were discharged from the hospital, had the AF before acute MI. Relative risk of death in patients with AF in this group (adjusted for age and sex) was significantly higher than this in patients without AF (OR=1.91; 95% CI 1.18-3.11; p=0.005). Conclusion. AF diagnosed in patients with acute MI at admission did not influence significantly hospital mortality. However, pre-existing AF increases significantly the risk of death in patients survived acute period of MI.